Análise da desertificação socioambiental no Bairro Jabotiana – Aracaju/SE - Leal, Elaine Vasconcelos Nascimento (2019)
In search of improvements in the quality of life and socio-environmental sustainability in cities, it was sought to ascertain the different urban configurations that allow or prevent the dynamics of the streets and the relation with the natural areas of the neighborhood, according to the ability to attract passers-by for the use of public spaces. With the large real estate growth, especially vertical condominiums, the Jabotiana neighborhood has presented scenarios resulting from the abandonment of neighborhood relations, walking in the neighborhood and identity with the natural environment in which it is inserted. Thus, the concept of "socio-environmental desertification" was constructed, whose analysis process in the Jabotiana neighborhood is the objective of this study, aiming to identify urban characteristics that interfere in the socio-environmental dynamics and contribute to related information, pertinent to the population and the public authorities. In order to reach this objective, some urban, geographic and sociological references are used as well as techniques that are limited to the collection of data referring to land uses; visual impermeability of facades; size of the courts; thermal comfort; physical conditions of sidewalks, squares and cycle paths; perception of the residents and of passers-by; insecurity; flows and activities of pedestrians in the streets; and information from public agency and local Non-governmental organization. As a result, and under the hypothetical-deductive method, it was found that there is "socio-environmental desertification" in the Jabotiana neighborhood and that the dynamicity of people in the streets, as well as the social-environmental relations of the residents, are in direct influence with the morphology of the neighborhood, but also with other socioeconomic and cultural factors that must be considered. Through this study, the discussion on "socio-environmental desertification" was deepened and it was possible to contribute important knowledge to sustainable urban planning.